2022
DOI: 10.3390/healthcare10122535
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates People to Receive Continuous COVID-19 Vaccine Booster Shots? An Expectation Confirmation Theory Perspective

Abstract: (1) Background: Abundant evidence has shown that the COVID-19 vaccine booster is highly effective against the Omicron variant. It is of great practical significance to explore the factors influencing the intention to receive COVID-19 booster shots. (2) Methods: We introduced expectation confirmation theory as the basis to construct a model of the factors of the vaccination intention for COVID-19 vaccine boosters. We obtained two batches of questionnaires through Chinese social platforms, with a valid sample si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The questionnaire is one of the important means to investigate public health behavior willingness and its influencing factors. This research method has been used in many previous studies on Chinese public epidemic prevention behavior [ 8 , 10 , 15 , 39 ]. Although it is difficult for survey researchers to obtain more profound and more nuanced ideas and understanding from participants compared with in-depth interviews, the closed-ended questionnaire has high efficiency, and the results can be processed uniformly for quantitative statistical analysis.…”
Section: Research Methods and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire is one of the important means to investigate public health behavior willingness and its influencing factors. This research method has been used in many previous studies on Chinese public epidemic prevention behavior [ 8 , 10 , 15 , 39 ]. Although it is difficult for survey researchers to obtain more profound and more nuanced ideas and understanding from participants compared with in-depth interviews, the closed-ended questionnaire has high efficiency, and the results can be processed uniformly for quantitative statistical analysis.…”
Section: Research Methods and Samplesmentioning
confidence: 99%
“…While a batch of studies has examined factors associated with people’s booster shot intention in China and worldwide [ 6 , 7 , 8 , 9 ], most have stopped at analyzing regular health considerations such as risk perceptions and perceived individual benefits. However, in China, harsh lockdowns have resulted in an extremely low incidence of new infections, causing the widespread perception of low infection susceptibility [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The filtering item was a simple mathematical calculation question, “100 + 100 = ?” We randomly inserted a screening question into the questionnaire. If the screening question was answered incorrectly, it meant that this subject was not serious in answering the questionnaire [ 66 ]. And it is likely that the questionnaire was filled out randomly.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few studies have made significant efforts to explore the factors influencing people's intention to receive COVID-19 vaccine booster. Understanding these factors is crucial for enhancing revaccinated acceptance, increasing revaccination rates, and reducing the risk of infection and severe illness [4][5][6][7][8][9]. For example, Kwok, Li (4) found that older age, smoking, experiencing no adverse effects from a previous COVID-19 vaccination, greater confidence in vaccines and collective responsibility, and fewer barriers in accessing vaccination services are associated with higher intention of receiving vaccine booster.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kwok, Li (4) found that older age, smoking, experiencing no adverse effects from a previous COVID-19 vaccination, greater confidence in vaccines and collective responsibility, and fewer barriers in accessing vaccination services are associated with higher intention of receiving vaccine booster. Liu, Lu (5) The Theory of Planned Behavior (TPB) has been widely utilized to interpret the intention of vaccination across various contexts [10]. It has been applied to understand the intention to vaccinate against H1N1 [11], HPV vaccination [12], whooping cough vaccination [13] [15], MMR vaccination [14], and hepatitis A vaccination [15].…”
Section: Introductionmentioning
confidence: 99%